ISOL A Jaspersian analysis of transcendence in Hermann Hesse’s Siddhartha - Deniz Akbar; Sri Sumaryani (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This study aims to break down how the process of transcendence (Transzendenz), as conceptualized by Karl Jaspers, operates in Hermann Hesse's novel Siddhartha. The analysis focuses on the moment of Siddhartha's encounter with Gautama Buddha, which has been proven to be the apt moment of transcendence. The existentialist pattern in Siddhartha's character strengthens Jaspers' argument regarding two important elements that enable transcendence (Transzendenz): limit situations (Grenzsituationen) and the encompassing (das Umgreifende). Through in-depth data analysis, three existentialist concepts were found, composed of four direct quotations from the conversation. All of them represent stages in Siddhartha's achievement of transcendence, which include awareness of one's limitations, rejection of dogma and external teachings, and an understanding of the importance of personal experience in finding the true meaning of life. This study contributes to the field of literature, particularly to the discourse of existentialism. Jaspers' concept offers a clear and concrete account of how transcendence is realized and narratively interpreted.